2020
DOI: 10.1002/ajcp.12463
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Risk Factors for Recidivism: For Whom do they Matter?

Abstract: Justice‐involved people vary substantially in their risk of reoffending. To date, recidivism prediction and prevention efforts have largely focused on individual‐level factors like antisocial traits. Although a growing body of research has examined the role of residential contexts in predicting reoffending, results have been equivocal. One reason for mixed results may be that an individual’s susceptibility to contextual influence depends upon his or her accumulated risk of reoffending. Based on a sample of 221… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
0
6
0
1
Order By: Relevance
“…Although interest in the connection between concentrated disadvantage and recidivism has increased, no empirical consensus exists regarding this relationship. Narrative reviews of the literature indicate tests of the concentrated disadvantage-recidivism relationship yield mixed results and that when associations are statistically significant, they are typically small (Jacobs & Skeem, 2021). Although small effects at the neighborhood level are common, the small effects of concentrated disadvantage and mixed results may stem from several factors that could lead to variation and weaken effects across studies, including threats to measurement and internal validity, and/or other factors related to study design, sample, and measurement.…”
mentioning
confidence: 99%
“…Although interest in the connection between concentrated disadvantage and recidivism has increased, no empirical consensus exists regarding this relationship. Narrative reviews of the literature indicate tests of the concentrated disadvantage-recidivism relationship yield mixed results and that when associations are statistically significant, they are typically small (Jacobs & Skeem, 2021). Although small effects at the neighborhood level are common, the small effects of concentrated disadvantage and mixed results may stem from several factors that could lead to variation and weaken effects across studies, including threats to measurement and internal validity, and/or other factors related to study design, sample, and measurement.…”
mentioning
confidence: 99%
“…We excluded current violence, as it was less a risk scale and more an indicator of the index offense, and because history of violence was substantively similar but more robust. Prior studies have indicated the overall validity of COMPAS in predicting recidivism ( 15 , 16 ), including in the study site ( 17 ), and support the predictive validity and reliability of the majority of the base scales ( 16 ). We conducted separate reliability and validity tests, finding that the majority of scales were internally consistent (see below) and showed signs of construct validity (i.e., all correlation coefficients were positive and, for the most part, correlated in theoretically anticipated directions).…”
Section: Methodsmentioning
confidence: 70%
“…Increased presence of social service providers was associated with decreased likelihood of recidivism, but this effect was diminished when potential demand outstripped service availability (Hipp et al, 2010). High levels of neighborhood socioeconomic disadvantage are consistently associated with higher likelihood of recidivism even after accounting for individual-level characteristics (Hipp et al, 2010;Jacobs & Skeem, 2020;kubrin & Stewart, 2006).…”
Section: Marginalization and Disadvantagementioning
confidence: 99%
“…Compared to the US noninstitutionalized adult population, adults on probation are significantly more likely to be racial/ethnic minorities, less likely to have completed high school, and more likely to have very low annual incomes (Phelps, 2018). In addition to individual-level marginalization, many people on probation live in neighborhoods or communities characterized by concentrated disadvantage and inadequate social services (Cobbina et al, 2014; Jacobs & Skeem, 2020). In California, an analysis of neighborhood characteristics and parole violations found that clients who lived in socioeconomically disadvantaged neighborhoods were more likely to abscond, but no more likely to commit other kinds of violations than clients from less disadvantaged neighborhoods (Grattet et al, 2009).…”
Section: Factors Associated With Probation Revocationmentioning
confidence: 99%